DRY NEEDLING SEBAGAI TERAPI NYERI MIOFASIAL SERVIKAL - Hanik Badriyah Hidayat; Annisa Oktavianti (NEURONA, 2020)
Cervical myofacial pain (CMP) is a common source of nonspecific chronic neck pain. Pain can be local, regional and can also it has many many trigger points (trigger points / TrPs). CMP causes pain in the area of the cervical muscles and surrounding fascia. Neck pain reduces quality of life, productivity; furthermore, it also causes disability so that it affects socioeconomically towards patients and the community.Treatment of cervical myofacial pain syndrome is still unsatisfactory due to its chronicity. Dry needing (DN) is one of the nonpharmacological therapy option that can be applied in CMP. DN reduces peripheral and central sensitization by eliminating sources of peripheral nociception (MTrPs area), modulating dorsal horn activity and activating central pain inhibitory pathways.Recently, the DN therapy has been rapidly develop in pain management. However, the effectiveness of DN therapy is still unclear. Therefore, knowledge about the role of DN in CMP is important to be known. This article will discuss the role of DN in cervical myofacial pain syndrome.Keywords: Cervical myofacial pain, dry needling, myofascial trigger points, therapy